PENGARUH PERBEDAAN pH LARUTAN HARA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PAKCOY DALAM SISTEM HIDROPONIK Nutrient Film Technique (NFT): - Huda, M Sunanil; Suheri, Herman; Nufus, Novita Hidayatun (AGROTEKSOS, 2023)
This study aims to determine the effect of differences in pH on the growth and yield of pakcoy ( Brassica rapa L.) cultivated in the Nutrient Film Technique (NFT) hydroponic system. The experiment was carried out from November 2022 to March 2023, at Unram Farming in Nyur Lembang Village, Narmada District, West Lombok Regency, West Nusa Tenggara (NTB). The experimental design used was a completely randomized design (CRD) with three treatments, namely pH = 5, pH = 6.5 and pH = 8, each of which was repeated nine times. The results showed that the treatment with different pH had a significantly different effect on the growth and yield of pakcoy on all parameters except for plant height at 6 and 12 HST and number of leaves at 6 HST. The best growth and yield of pakcoy was obtained from P2 treatment (pH: 6.5), while the worst growth and yield of pakcoy was obtained from P3 treatment (pH: 8).